2013
DOI: 10.1016/j.nlm.2013.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Egr-1 increases in the prefrontal cortex following training in the context preexposure facilitation effect (CPFE) paradigm

Abstract: The context pre-exposure facilitation effect (CPFE) is a modified form of standard contextual fear conditioning that dissociates learning about the context during a preexposure phase from learning the context-shock association during an immediate shock training phase conducted on separate days. Fear conditioning in the CPFE is an associative process in which only animals that are preexposed to the same context they are later given an immediate shock in demonstrate freezing when tested for conditioned fear memo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
94
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(123 citation statements)
references
References 69 publications
24
94
5
Order By: Relevance
“…However, Egr-1 mRNA is also increased following exposure to unpredictable situations and exposure to novel contexts – suggesting its role in learning contextual information may be quite complex [15, 16, 2527]. While a number of studies have examined the functional role and molecular changes occurring within the hippocampus and amygdala during different phases of learning in sCFC and the CPFE, recent evidence has begun to point to a role for the prefrontal cortex (PFC) in contextual fear learning [10, 19, 20, 28, 29]. Although the neuroanatomical pathways between the PFC, hippocampus, and amygdala are fairly well characterized, the function of the PFC in contextual fear conditioning is just starting to be explored [3033].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Egr-1 mRNA is also increased following exposure to unpredictable situations and exposure to novel contexts – suggesting its role in learning contextual information may be quite complex [15, 16, 2527]. While a number of studies have examined the functional role and molecular changes occurring within the hippocampus and amygdala during different phases of learning in sCFC and the CPFE, recent evidence has begun to point to a role for the prefrontal cortex (PFC) in contextual fear learning [10, 19, 20, 28, 29]. Although the neuroanatomical pathways between the PFC, hippocampus, and amygdala are fairly well characterized, the function of the PFC in contextual fear conditioning is just starting to be explored [3033].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have begun examining activation of the PFC during contextual fear learning using the CPFE paradigm in developing rats [29, 34]. We have found rats that learn the CPFE via preexposure to the training context (relative to rats preexposed to an alternate context) show increased Egr-1 mRNA levels in the prelimbic and infralimbic regions of the PFC following the context-shock learning phase.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Asok and colleagues demonstrated that increased expression of zif268 within the prefrontal cortex is associated with contextual fear conditioning in the context of the pre-exposure facilitation effect paradigm. They also found fear-conditioned rats displayed significantly more zif268 mRNA expression in the infralimbic, prelimbic, and orbitofrontal cortices than the alternate context pre-exposed control rats (Asok et al 2013). Further experiments are needed to clarify the role of zif268 in these structures on extinction.…”
Section: Discussionmentioning
confidence: 97%
“…In addition to possible differential involvement of the hippocampus and amygdala, it is possible that NMDA receptor antagonism disrupts mPFC plasticity occurring during the CPFE. Our lab has previously reported an increase in the immediate early-growth response gene 1 ( Egr-1 ) in the mPFC in PD31 rats after context-shock association training in the CPFE [5, 6]. It is possible that there may be differential contributions of NMDA receptors in the BLA, DHPC, and mPFC in postshock and retention test freezing within the CPFE.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that the CPFE emerges between postnatal day (PD) 17 and 24 in the rat [14], at which point it depends on hippocampal NMDA receptors and on conjunctive-rather than feature-based context representations in developing rats [15]. We have also shown that the CPFE engages plasticity and drives immediate early gene expression in the hippocampus, amygdala, and prefrontal cortex in adolescent rats [5, 6]. …”
Section: Introductionmentioning
confidence: 99%